Marcas político-ideológicas na fala da presidente Dilma Rousseff na Assembléia Geral da ONU/2011 : o funcionamento do discurso sobre a mulher - Bispo, Katia Santana (2014)
This thesis aims to investigate the functioning of talking about the woman , in a speech by the President of Brazil , Dilma Rousseff , representative of the Workers Party ( PT) , at the opening of the debate of the 66th General Assembly of the United Nations ( UN) , held in New York in the United States in September 2011. Whereas important elements of discourse , we find the conditions of production in which the speech was made , the position and social position occupied by the subject -speaker as well as the political- ideological and discursive memory brands in verified statement and that made said ( or not said ) made sense. In support of our study , support us on a theoretical and methodological apparatus of Discourse Analysis of the French line , made from a link between theories of language , from a pragmatic- discursive perspective sustained by authors like Pêcheux Orlandi and Charaudeau. During the research, we note that President Dilma Rousseff as the subject which was constituted authority , transformed his own social and historical condition , built positive images of themselves and at the same time , deconstructed and shifted linguistic- discursive contexts derived senses patriarchal domination.